2006
DOI: 10.1248/bpb.29.592
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Larvicidal, Adulticidal and Acaricidal Activity of Two Geometrical Butylidenephthalide Isomers

Abstract: Butylidenephthalide, the components of Angelica acutiloba var. sugiyamae HIKINO (Apiaceae) has the biological activities, such as centrally acting muscle relaxant 1) and antispasmodic effects 2) with characteristic odor. In our previous work,3) (Z)-butylidenephthalide was isolated as the potent insecticidal compound against adults and larvae of Drosophila melanogaster. Recently, Ahn et al. reported that butylidenephthalide was active constituent of Cnidium officinale against Dermatophagoides farinae and Tyroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was potently toxic to the adults of fruit fly, Drosophila melanogaster, and the effective performance of its E-and Z-two isomers make no difference in the bioassays. This compound also showed acaricidal activity against two house dust mites, Dermatophagoides farinae and Tyrophagus putrescentiae 24 . Additionally, a published article reported that 3-butylidenephthalide was toxic to B-and Q-biotypes females of Bemisia tabaci in leaf-dip bioassay LC 50 254.2 and 586.3 ppm, respectively .…”
Section: Repellent Activitymentioning
confidence: 90%
“…It was potently toxic to the adults of fruit fly, Drosophila melanogaster, and the effective performance of its E-and Z-two isomers make no difference in the bioassays. This compound also showed acaricidal activity against two house dust mites, Dermatophagoides farinae and Tyrophagus putrescentiae 24 . Additionally, a published article reported that 3-butylidenephthalide was toxic to B-and Q-biotypes females of Bemisia tabaci in leaf-dip bioassay LC 50 254.2 and 586.3 ppm, respectively .…”
Section: Repellent Activitymentioning
confidence: 90%
“…There are studies concerning antiproliferation and antitumor potential of this group of compounds. Furthermore, the authors also report their insecticidal properties (Chu, Jiang, & Liu, ; Kan, Cho, Rudd, & Lin, ; Tsai et al, ; Tsukamoto et al, ). Another significant bioactivities of phthalides involve antifungal and antibacterial effects (Sim & Shin, ).…”
Section: Introductionmentioning
confidence: 98%